Historical Analysis of National Subjective Wellbeing Using Millions of Digitized Books - Thomas Hills; Eugenio Proto; Daniel Sgroi (Center for Economic Studies and ifo Institute (CESifo), 2016)
We present the first attempt to construct a long-run historical measure of subjective wellbeing using language corpora from millions of digitized books for the USA, UK, Germany, France, Italy and Spain. While existing measures go back at most to the 1970s, our measure goes back at least 200 years further. Our measure correlates positively with existing wellbeing measures where available. The relationship with life expectancy is significant and positive. Infant mortality correlates negatively and independently from the effect of life expectancy. There is no correlation with GDP. Econometric analysis of the data is undertaken to control for potentially confounding factors.
Keywords: N30; N40; O10; D60; 330; historical subjective wellbeing; big data; Google Books; GDP; conflict; Easterlin paradox